Study of Various Parameters that Influence the Content of Exhaled Breath Condensate Used in the Diagnosis of Gastroesophageal Reflux Disease - Greguš Michal (Hungarian Journal of Industry and Chemistry, 2018)
In this work, various parameters that influence the ionic content and pH of exhaled breath condensate in of the noninvasive diagnosis of gastroesophageal reflux disease were studied. Exhaled breath condensate samples were collected using a miniature and inexpensive sampling device. Capillary electrophoresis with contactless conductometric detection was used to monitor the ionic content of exhaled breath condensate. Background electrolyte composed of 20 mM of 2-(N-Morpholino)ethanesulfonic acid, 20 mM of L-Histidine, 2 mM of 18-Crown-6 and 30 M of cetyltrimethylammonium bromide facilitated the rapid separation of anions and cations, both in less than 2 minutes. The possibility of contamination of the exhaled breath condensate by saliva is discussed in detail. The day-to-day repeatability (n=5) of the ionic content and pH of the exhaled breath condensate was studied and was satisfactory, reflecting mainly the physiological variability